2018
DOI: 10.3389/fimmu.2018.00532
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Immunization: Rationale, Current State, and Future Prospects

Abstract: Infections take their greatest toll in early life necessitating robust approaches to protect the very young. Here, we review the rationale, current state, and future research directions for one such approach: neonatal immunization. Challenges to neonatal immunization include natural concern about safety as well as a distinct neonatal immune system that is generally polarized against Th1 responses to many stimuli such that some vaccines that are effective in adults are not in newborns. Nevertheless, neonatal im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 91 publications
(102 reference statements)
1
43
0
1
Order By: Relevance
“…The ability of live vaccines such as BCG to induce heterologous immunity raises the possibility of leveraging such broadly protective effects in the development of novel vaccine formulations (Whittaker et al, 2018a), in the form of "trained immunity-based" vaccines (Sanchez-Ramon et al, 2018). Firstly, increased awareness of innate memory may be employed to define new classes of vaccine adjuvants (Topfer et al, 2015), crucial tools to optimize current vaccines and develop new ones (Dowling and Levy, 2015).…”
Section: Bcg As a Model To Build Next Generation Vaccinesmentioning
confidence: 99%
“…The ability of live vaccines such as BCG to induce heterologous immunity raises the possibility of leveraging such broadly protective effects in the development of novel vaccine formulations (Whittaker et al, 2018a), in the form of "trained immunity-based" vaccines (Sanchez-Ramon et al, 2018). Firstly, increased awareness of innate memory may be employed to define new classes of vaccine adjuvants (Topfer et al, 2015), crucial tools to optimize current vaccines and develop new ones (Dowling and Levy, 2015).…”
Section: Bcg As a Model To Build Next Generation Vaccinesmentioning
confidence: 99%
“…As opposed to the few vaccines mentioned above, most vaccines are only administered after the neonatal phase has passed. Starting at 2 months of age, vaccines administered to infants include rotavirus vaccine (2 and 4 months), diphtheria, pertussis, tetanus (DTaP) (2, 4, 6, and 15-18 months), Hib conjugate (2, 4, 6, 12-15 months), pneumococcal conjugate (PCV; 2, 4, 6, 12-15 months), IPV (2, 4, 6-18 months), seasonal influenza (6 months and older), measles, mumps, and rubella (MMR) (12 months), varicella (12 months), and hepatitis A (12-18 months) (reviewed in [70,79]). The major reason for this delay is two-fold; first, there is an age-dependent increase in seroconversion rates if vaccination is delayed and also this delay avoids much of the potential problem of maternal antibody interference [13,23,26].…”
Section: Lessons From Successful Neonatal Vaccinesmentioning
confidence: 99%
“…For example, transcriptomic analyses showed early gene signatures following vaccination were predictive of subsequent measures of immunogenicity for seasonal influenza [135]. These high-dimensional methodologies could be applied to characterization of neonatal vaccine-induced molecular signatures that correspond to protection [79,136,137]. The importance of formulation to vaccine effectiveness is often overlooked, and hence there is also a need for research into development of new and improved formulations and stable delivery systems to improve neonatal vaccine immunogenicity.…”
Section: Expert Opinionmentioning
confidence: 99%
“…(ii) Neonatal immunization. Despite challenges inherent to vaccine development in the very young, there is a robust rationale for continued vaccine development for this population, including (a) birth is the most reliable point of health care contact and therefore neonatal vaccines achieve high population penetration; (b) neonatal immunization is a logical approach to protect preterm infants, who represent ϳ11% of all live births and are often born prior to transfer of maternal antibodies (MatAbs) (such that maternal immunization may not be protective); and (c) growing evidence that the heterologous benefits of certain vaccines such as BCG may be greatest in early life (8).…”
mentioning
confidence: 99%
“…Vaccines currently given at birth provide strong evidence that protective immunity can be induced by vaccination and can also inform on the potential of neonates to develop specific immune responses and on the impact of cofactors. Studies of BCG immunization have demonstrated that Th1 responses can be induced at birth and that BCG vaccination can have heterologous effects on the response to other vaccines and on overall infant mortality (8,10). Studies of hepatitis B and oral polio immunization at birth indicated that priming of memory B cells can be achieved in early life, allowing the option to immunize infants at birth.…”
mentioning
confidence: 99%